2003
DOI: 10.1074/jbc.m213290200
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Microsomal Prostaglandin E Synthase-1 in Tumorigenesis

Abstract: Microsomal prostaglandin E 2 synthase-1 (mPGES-1) is a stimulus-inducible enzyme that functions downstream of cyclooxygenase (COX)-2 in the PGE 2 -biosynthetic pathway. Given the accumulating evidence that COX-2-derived PGE 2 participates in the development of various tumors, including colorectal cancer, we herein examined the potential involvement of mPGES-1 in tumorigenesis. Immunohistochemical analyses demonstrated the expression of both COX-2 and mPGES-1 in human colon cancer tissues. HCA-7, a human colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 68 publications
9
168
1
3
Order By: Relevance
“…Our previous immunohistochemical analyses demonstrated a preferential localization of mPGES-1 in MF-like cells infiltrating the stromal tissues in proximity to cancer cells (Kamei et al, 2003). As shown in Figure 2b, mPGES-1 was expressed in leukocytes invading into the stroma of the colon carcinoma region in the AOM-treated mice.…”
Section: Reduced Growth Of Intrasplenically Transplanted Tumor Cells mentioning
confidence: 55%
See 3 more Smart Citations
“…Our previous immunohistochemical analyses demonstrated a preferential localization of mPGES-1 in MF-like cells infiltrating the stromal tissues in proximity to cancer cells (Kamei et al, 2003). As shown in Figure 2b, mPGES-1 was expressed in leukocytes invading into the stroma of the colon carcinoma region in the AOM-treated mice.…”
Section: Reduced Growth Of Intrasplenically Transplanted Tumor Cells mentioning
confidence: 55%
“…These results suggest that overproduction of mPGES-1-derived PGE 2 is not sufficient for initiating colon carcinogenesis, but is crucially involved in ACF formation. We previously reported that the forcible transfection of mPGES-1 in combination with COX-2 into HEK293 cells led to cellular transformation with a concomitant and robust increase in PGE 2 (Kamei et al, 2003). It was also shown that overexpression of COX-2 induced genomic instability in MCF10A breast cancer cells (Singh et al, 2007) and that AOM-induced colon tumors in mice were chromosomally stable and were characterized by low-level microsatellite instability (Guda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overexpression of COX-2 has been linked to the development of various types of human cancers [65,66]. Several reports have indicated that COX-2 affects the invasiveness of cancer cells [67][68][69]. Gastric fibroblasts stimulate the invasiveness of scirrhous gastric cancer cells, while a selective COX-2 inhibitor, JTE-522, decreases HGF production from gastric fibroblasts by suppression of PGE2 productions, thus resulting in decreased invasion ability of gastric cancer cells [62,70].…”
Section: Therapies To Target the Cancer-stromal Interactionsmentioning
confidence: 99%